Creative STEM activities for Orang Asli students at SK Sg. Melut / Dr. Nurwahida Zulkifli and Assoc. Prof. Dr. Mahmathi Karuppannan - Zulkifli, Nurwahida; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
Volunteering at a primary school can be a rewarding experience especially when you are able to make a positive impact on the lives of young children. On the 3rd of May 2023, 6 lecturers from the Faculty of Pharmacy namely Dr. Nurwahida Zulkifli, Mdm. Farhana Fakhira Ismail, Mdm. Nik Ateerah Rasheeda Mohd Rocky, Mdm. Nor Elyzatul Akma Hamdan, Mdm. Nursabiha Md. Hussin and Ms. Zakiah Mohd Noordin volunteered in a program called STEM @Melut at Sekolah Kebangsaan Sungai Melut, Sepang. This school caters mainly for Orang Asli children and there are about 65 students.